Sintering properties of ZnO-TiO2 composite ceramics - Kopiha, V.; Sutharsini, U. (University of Jaffna, 2021)
Among various semiconductor oxides, ZnO and TiO2 composite have been used wide variety of applications such as solar cells, varistors, and sensors. In this work effect of sintering temperature and sintering time on ZnO - TiO2 composite were studied. Five different mole ratio (ZnO : TiO2 = 9:1, 4:1, 7:3, 3:2, and 1:1) of ZnO and TiO2 powder was mixed by using mortar and pestle. Mixed powder was pressed into palette before sintered at temperatures 600, 700, 800, 900 and 1000˚C for one and two hours. In order to obtain reference pattern, pure ZnO and TiO2 also sintered. Sintered samples were then characterized by using X ray Diffraction Spectrometer (XRD). At the sintering temperature 600˚C, only the peaks corresponding to ZnO and TiO2 was observed. Regardless of mole ratio, Zn2TiO4 and Zn2Ti3O8 composites were started to develop at the sintering temperature 700˚C for one hour. The developed peaks corresponding to Zn2TiO4 and Zn2Ti3O8 were matched with JCPDS number 00-002-1033 and 00-013-0471 respectively. XRD Pattern for ZnO-TiO2 composite along with pure ZnO and TiO2 sintered at 1000˚C for two hours is shown in the Figure. According to the XRD pattern, as the sintering time is increased, additional peaks corresponding to ZnTiO3 (JCPDS number 00-015-0591) also started developed at 700˚C. Phase development of the composite is increased with increasing sintering temperature and sintering time.
Keywords: ZnO-TiO2 composite; XRD; Sintering